MENINGKATKAN MOTIVASI BELAJAR SISWA TERHADAP MATA PELAJARAN IPS DENGAN PENERAPAN MEDIA PEMBELAJARAN AUDIO VISUAL DI KELAS IV SDN 3 SUKASARI - Aura Futri Patimah; Rizki Hadiwijaya Zulkarnaen; Deni Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning motivation of fourth-grade students in Social Studies (IPS) at SDN 3 Sukasari, due to the lack of engaging and varied learning media. The aim of this study was to improve students’ learning motivation through the use of audio-visual media such as videos and PowerPoint (PPT). The research used a Classroom Action Research (CAR) method involving 34 students. The results showed a significant increase in learning motivation. The average motivation at the pre-action stage was 22%. After using audio-visual media in cycle I, it increased to 76.38%, and in cycle II it further increased to 94.12%. The overall improvement from pre-action to cycle II was 72.12%. These findings indicate that audio-visual media is effective in enhancing students’ learning motivation. Therefore, it is recommended for use in elementary Social Studies learning